Basic Football Techniques for High School Students - Ridwan, Andi; Adil, Ahmad; Sudirman, Sudirman (Sains Global Institut, Indonesia, 2023)
This research aims to find out: (1) Basic techniques for heading the ball among students, (2) Basic techniques for dribbling the ball among students, (3) Basic techniques for passing and holding the ball among students, and (4) Basic techniques for shooting the ball. This research is a type of survey research. The population of this study were all students of SMA Negeri 2 Sinjai, specifically for boys, classes X and XI with a total research sample of 30 students selected by random sampling. The data analysis techniques used are descriptive, data normality, and categorization using the SPSS Version 22.00 system at a significance level of 95% or a0,05. Based on the results of data analysis, this research concludes that: (1) The basic technique of ball heading for students at SMA Negeri 2 Sinjai is in the Medium category; (2) Basic techniques for dribbling the ball for SMA Negeri 2 Sinjai students are in the Medium category, (3) Basic techniques for passing and holding the ball for students at SMA Negeri 2 Sinjai are in the Medium category, and (4) Basic shooting techniques for SMA Negeri 2 students Sinjai is in the Medium category.